DEVIATIONS IN THE USE OF FIXED-TERM EMPLOYMENT AGREEMENT IN THE OUTSOURCING SYSTEM - Novela, Devina; Lie, Gunardi (Awang Long Law Review, 2025)
Outsourcing has become a choice for companies in dealing with market competition to reduce production costs and increase company flexibility. In practice, outsourcing uses fixed-term employment agreement to form a bond between employers and workers. However, disputes often arise between the two parties regarding rights and obligations that are frequently violated, especially by companies that take advantage of the existence of fixed-term employment agreement to bind outsourced workers. The issues to be examined are the misuse of fixed-term employment agreement in the outsourcing system in The Industrial Relations Court Decision No. 400/Pdt.Sus-PHI/2022/PN.Jkt.Pst. and the application of the principles of protection and legal certainty for outsourced workers in cases of misuse of fixed-term employment agreement in the aforementioned case. The author applies a normative research method with primary legal materials, namely positive labor law and secondary legal materials such as books and legal journals through legal literature study techniques. With a regulatory approach, the data is then analyzed using qualitative methods to compile the data into information. Through the conflict between the law and its implementation, it can be concluded that the form of deviation that occurs is due to the repeated use of agreements and the existence of a pseudo-employment relationship that gives rise to legal consequences for which the company must be held accountable. The application of the principles of legal protection and legal certainty is a form of justice obtained by workers so that the agreement that has been made is binding on both parties. Through the conflict between the law and its implementation, it can be concluded that the form of deviation that occurs is due to the repeated use of agreements and the existence of pseudo-employment relationships that give rise to legal consequences for which the company is liable. The application of the principles of legal protection and legal certainty is a form of justice for workers, so that the agreements that have been made are not merely a formality but provide real protection.